Analisis Willingness To Pay Pada Wisata Bukit Matang Kaladan Desa Tiwingan Lama Kecamatan Aranio Kabupaten Banjar Kalimantan Selatan - Muhammad Rauhan Fikri; Noor Rahmini (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research was conducted to find out: (1) To analyze the willingness oftourists to pay (Willingness to Pay) in Bukit Matang Kaladan Tourism (2) To find outwhether factors of education, income, number of family members, and travel costs affecttravel value (Willingness to Pay) Bukit Matang Kaladan Tourism. (3) To find out themost dominant factors influencing tourists' willingness to pay (Willingness to Pay)towards the Bukit Matang Kaladan attraction.The analytical method used is the Willingness to Pay (WTP) and Regressionapproach with research variables: education, income, number of family members, andtravel costs. According to the criteria using a questionnaire, the data source is primarydata obtained through direct interviews with Bukit Matang Kaladan tourists.The calculations using the Willingness to Pay (WTP) and Regression Approachmethod show the average willingness to pay is Rp 11,260. If there is an increase inquality, the average amount that is willing to be added by respondents is Rp. 7,760. Theaverage willingness to pay respondents to travel to Bukit Matang Kaladan is Rp. 19,020.This study's significant variables are education, income and travel cost, and theinsignificant variable is the number of family members. At the same time, the mostdominant factor in this study is travel costs.